Neutrophil diversity in inflammation and cancer - Carnevale, Silvia; Di Ceglie, Irene; Grieco, Giovanna; Rigatelli, Anna; Bonavita, Eduardo; Jaillon, Sebastien (Frontiers in Immunology, 2023)
Neutrophils are the most abundant circulating leukocytes in humans and the first immune cells recruited at the site of inflammation. Classically perceived as short-lived effector cells with limited plasticity and diversity, neutrophils are now recognized as highly heterogenous immune cells, which can adapt to various environmental cues. In addition to playing a central role in the host defence, neutrophils are involved in pathological contexts such as inflammatory diseases and cancer. The prevalence of neutrophils in these conditions is usually associated with detrimental inflammatory responses and poor clinical outcomes. However, a beneficial role for neutrophils is emerging in several pathological contexts, including in cancer. Here we will review the current knowledge of neutrophil biology and heterogeneity in steady state and during inflammation, with a focus on the opposing roles of neutrophils in different pathological contexts.